Reaction kinetics and molecular characterization of the compounds formed by photosensitized degradation of the plastic additive bisphenol A in the atmospheric aqueous phase - Yiting Wang; Qingxin Deng; Yiqun Wang; Pan Li; Biao Jin; Jiangping Liu; Peng Cheng; Marcello Brigante; Dario D’Antuono; Luca Carena; Hui Chen; Davide Vione; et al. (Scientific Reports)
Abstract Bisphenol A (BPA, 4,4'-(propane-2,2-diyl)diphenol) is a common plasticizer that is very widespread in the environment and is also found at significant concentrations in the global oceans, due to contamination by plastics. Here we show that triplet sensitization is an important degradation pathway for BPA in natural surface waters, which could prevail if the water dissolved organic carbon is above 2–3 mgC L−1. Bromide levels as per seawater conditions have the potential to slow down BPA photodegradation, a phenomenon that could not be offset by reaction of BPA with Br2 •− (second-order reaction rate constant of (2.54 ± 0.09) × 108 M−1 s−1). Ultra-high resolution mass spectrometry revealed that the presence of inorganic salts (NaCl and NaBr) markedly increased the complexity of the observed CHO product compounds formed upon photosensitized degradation of BPA. The obtained results suggest that bisphenols can be efficiently removed by photosensitized reactions and generate higher number of oligomers and polyaromatic compounds in the sea surface and liquid water of marine aerosols compared to freshwaters and/or dilute cloud-water. Considering that polyaromatic compounds absorb solar actinic radiation, these results suggest that inorganic salts could significantly affect the photosensitized degradation of bisphenols and consequently influence the light-absorbing properties of marine aerosols and, ultimately, the Earth’s radiative balance.